The Effect of Fat Pad Modification during Ablation of Atrial Fibrillation: Late Gadolinium Enhancement MRI Analysis. - Higuchi, Koji; Akkaya, Mehmet; Koopmann, Matthias; Blauer, Joshua J.E.; Burgon, Nathan S.; Damal, Kavitha; Ranjan, Ravi; Kholmovski, Eugene; Macleod, Rob S.; Marrouche, Nassir F. (Pacing & Clinical Electrophysiology, 2013)
Background Magnetic resonance imaging (MRI) can visualize locations of both the ablation scar on the left atrium (LA) after atrial fibrillation (AF) ablation and epicardial fat pads (FPs) containing ganglionated plexi (GP). Methods We investigated 60 patients who underwent pulmonary vein antrum (PVA) isolation along with LA posterior wall and septal debulking for AF. FPs around the LA surface in well-known GP areas (which were considered as the substitution of GP areas around the LA) were segmented from the dark-blood MRI. Then the FP and the ablation scar image visualized by late gadolinium enhancement (LGE)-MRI on the LA were merged together. Overlapping areas of FP and the ablation scar image were considered as the ablated FP areas containing GP. Patients underwent 24-hour Holter monitoring after ablation for the analysis of heart rate variability. Results Ablated FP area was significantly wider in patients without AF recurrence than those in patients with recurrence (5.6 ± 3.1 cm2 vs 4.2 ± 2.7 cm2, P = 0.03). The mean values of both percentage of differences greater than 50 ms in the RR intervals (pRR > 50) and standard deviation of RR intervals over the entire analyzed period (SDNN), which were obtained from 24-hour Holter monitoring 1-day post-AF ablation, were significantly lower in patients without recurrence than those in patients with recurrence (5.8 ± 6.0% vs 14.0 ± 10.1%; P = 0.0005, 78.7 ± 32.4 ms vs 109.2 ± 43.5 ms; P = 0.005). There was a significant negative correlation between SDNN and the percentage of ablated FP area (Y = −1.3168X + 118.96, R2 = 0.1576, P = 0.003). Conclusion Extensively ablating LA covering GP areas along with PVA isolation enhanced the denervation of autonomic nerve system and seemed to improve procedural outcome in patients with AF.